Manajemen Kesiswaan dalam Pengembangan Mutu Pendidikan Islam di Era Revolusi Industri 4.0 - Ahmad Fauzi (At- Ta'lim : Jurnal Pendidikan, 2019)
At the level of reality, student management studies are an important part in building and developing the quality of Islamic education in the era of industrial revolution 4. 0. Management in the field of student affairs in essence is still considered to be not optimal, especially for Islamic education institutions, as an effort to give birth to the intended quality, can be started from student management, by planning learning activities, carrying out continuous guidance for students in developing their abilities. Student management can be started from planning, student admission, grouping, recording attendance of students, fostering student discipline, regulating student transfer, graduation and ending with the implementation of the program. In addition, student management is part of a variety of other managerial activities, therefore student management can run well if it considers several aspects, namely; a) the role of the teacher is expected to be responsive in determining various policies in the field of student affairs, b) student services must be based on needs, taking into account the characteristics of students c) student management is expected to create orderly and pleasant learning situations so that students’ personalities grow and develop, d) effectiveness student management requires funding and adequate facilities. Thus various management activities basically aim to achieve a goal, namely the creation of quality education in accordance with the wishes of today’s society. Keywords: management, student affairs, education quality in the era of industrial Revlution 4.0